Getting there, getting by, getting through the UPCB survival handbook. (Board of Student Services and the Public Information and Publications Office, UP College Baguio, 1993)
Intended for the incoming students of the University of the Philippines-College of Baguio. It aims to help the students find their way around, introduce them to the world of UPCB and to help them through the freshmen year.